Psychological factors in the diagnosis and pathogenesis of stiff-man syndrome - Henningsen, Peter; Clement, Ulrich; Küchenhoff, Joachim; Simon, Fritz B.; Meinck, Hans-Michael (Neurology, 1996)
Retrospective psychological evaluation of nine patients with stiff-man syndrome (SMS), seven of whom evidenced autoimmune disease, revealed a characteristic set of psychological symptoms or features: Major stressful life events preceded the development of permanent symptoms by 6 months or less (seven patients); transient motor symptoms occurred in emotionally distressing situations months or even years before the onset of a permanent motor deficit (five patients); after onset, similar situations specifically precipitated or augmented stiffness and spasms (five patients). We also found task-specific fear resembling agoraphobia (six patients) and loss or invalidation of one or both parents, or loss of home, in childhood (seven patients). Eight patients were initially misdiagnosed as having psychogenic movement disorder. We conclude that the common misdiagnosis of SMS as a psychogenic movement disorder is due to the compelling association of a set of salient psychological features, bizarre and fluctuating motor symptoms, and lack of approved neurologic signs. - NEUROLOGY 1996;47: 38-42
Gesehen am 23.07.2024